Layanan Informasi Pribadi Sosial untuk Meningkatkan Penyesuaian Diri dalam Pergaulan Siswa SMP - Risma Sutihat; Veny Agustini Prianggita (Indonesian Journal of Educational Counseling, 2020)
SOCIAL PERSONAL INFORMATION SERVICES TO IMPROVE SOCIAL ADJUSTMENT IN JUNIOR HIGH SCHOOL STUDENTS. The aim of this study was to determine the effectiveness of social personal information services to improve students’ self-adjustment in socializing at school for seventh grade students of SMP Negeri 1 Saketi in the 2019/2020 academic year. This study used pre-test and post-test instruments which showed an increase in every aspect that influenced social adjustment at school through social personal information services. The data analysis states that the alternative hypothesis (Ha) is accepted, namely that social personal information services are effective for increasing social adjustment at school for seventh grade students of SMP Negeri 1 Saketi because students’ adjustment in socializing at school is influenced by many aspects. The aspects that determine or influence the adjustment of students in the association of students at school include: 1) Understanding themselves, including being able to adjust to the environment they occupy, understand the characteristics of adolescents, understand their interests and talents, understand the physical and spiritual condition; 2) Knowing the environment means that after understanding the characteristics of adolescents and the duties of adolescents, they can apply ways of adapting themselves to social interactions in schools in particular and outside in general; and 3) The social adjustment process at school leads students to good associations and limits students to bad associations.